A Quantitative Study of the Strategic Arms Race in the Missile Age: A Reply - McGuire, Martin (The Review of Economics and Statistics, 1981)
Allen, R. G. D., Mathematical Economics (London: Macmillan, 1956). Barnaby, F., Inevitable Conflict, New Scientist (August 25, 1979), 581-583. Hendry, D. F., and T. von Ungern-Sternberg, Liquidity and Inflation Effects on Consumers' Expenditure, in A. S. Deaton (ed.), Essays in the Theory and Measurement of Consumers' Behaviour (Cambridge: Cambridge University Press, 1980). McGuire, Martin C., A Quantitative Study of the Strategic Arms Race in the Missile Age, this REVIEW 59 (Aug. 1977), 328-339. Phillips, A. W. H., Stabilisation Policy in a Closed Economy, Economic Journal (June 1954). Sargan, J. D. Some Tests of Dynamic Specification for a Single Equation, Econornetrica 48 (May 1980), 879897.